Integrating blueprint and process: A structured flexibility approach t o development management - Brinkerhoff, Derick W.; Ingle, Marcus D. (Public Administration and Development, 1989)
Managing socio-economic development according to highly detailed pre-i mplementation plans rigidly applied has not had a high degree of succe ss in generating sustained progress in the world's poorer nations. At the other end of the spectrum is the process approach that avoids spec ifying targets in advance, and concentrates upon building problem-solv ing capacity among the people involved. Many international donor and d eveloping country agencies favour the blueprint model, despite its per formance weaknesses, for its control and specificity. The process appr oach is limited by its lack of fit with agency procedures and incentiv es. This article discusses a structured flexibility approach to develo pment management that integrates the blueprint model's planned structu ring of action with the process model's flexibility and iterative lear ning orientation. This blend provides the basis for the programmatic a nd financial accountability required to obtain support from donor and developing country bureaucracies, and facilitates adaptive management to deal with uncertain and changing task environments. Case examples f rom the Caribbean, Portugal, and Pakistan illustrate the application o f the structured flexibility approach.
Keywords: IMPORTANT